Students’ Attitude Toward the Use of Reading Aloud in Learning Reading Skills at SMP Muhammadiyah 6 Padang - Hikmah, Sri; Zainil, Yetti (Universitas Negeri Padang, 2024)
This study aims to analyze students' attitudes towards the use of reading aloud in learning reading skills at SMP Muhammadiyah 6 Padang. The researcher employed a mixed-methods approach, involving a total population of 204 students from grades 7, 8, and 9, as well as English teachers at SMP Muhammadiyah 6 Padang. The research sample, obtained through simple random sampling, comprised 25% of the student population, totaling 51 students, and two English teachers. Quantitative research was conducted using a questionnaire to analyze students' attitudes towards the use of reading aloud in learning reading skills at SMP Muhammadiyah 6 Padang. Meanwhile, qualitative research was carried out to analyze the extent to which teachers utilize reading aloud in teaching reading skills. The research findings indicate that students have positive attitude towards affective, cognitive, and behavioral components in learning reading skills. Therefore, it can be concluded that students feel that reading aloud helps and motivates them in learning English reading skills. Interviews with two English teachers also revealed skillful practices of reading aloud, aligning with best practices in reading aloud.